3D printing shape memory polymer of laminated multi-component metamaterial towards optimization of auxetic and shape recovery behaviors - Liu, Yuheng (2024)
With the development of multifunctional metamaterials, auxetic shape memory metamaterials have attracted extensive attentions. However, the combination of material property into structural metamaterial has not been fully understand. In this study, a 3D printing laminated multi-component metamaterial has been manufactured using the viscoelastic and elastic shape memory polymers (SMPs), to achieve a tailorable release rate of strain energy for optimization of auxetic and shape recovery behaviors. A synergistic effect of laminated structure arrangement and cell radius has been identified as the driving force to achieve the auxetic behavior (for metamaterial), high storage strain energy (for yielding strength) and release rate (for shape recovery behavior). Finally, the auxetic, yielding, and shape recovery behaviors have been experimentally tested, to verify the effectiveness of the finite element method results. And a good agreement between them has been achieved. This study is expected to provide a design guideline for auxetic and shape recovery behaviors of laminated multi-component SMP metamaterial.